Digital transformation and educational quality in higher education institutions: evidence from the Rohilkhand region of Uttar Pradesh - Dixit, Pravendra; Singh, P. B. (Journal of Advanced Education and Sciences, 2026)
Digital technologies are reshaping teaching, learning, and student engagement across higher education institutions. In India, policy initiatives such as the National Education Policy (NEP) 2020 and the Digital India programme have accelerated the integration of digital technologies across universities and colleges. Despite these developments, empirical evidence on the contribution of digital transformation to educational quality remains limited, particularly in regional higher education systems. This study examines the relationship between digital transformation and educational quality in higher education institutions located in the Rohilkhand region of Uttar Pradesh. The study conceptualizes digital transformation through four key dimensions: digital infrastructure, faculty digital competence, institutional support, and technology-enabled teaching practices. Educational quality is assessed through teaching effectiveness, student engagement, learning outcomes, and academic support services. A quantitative research design is employed to investigate the proposed relationships. Data are collected from students and faculty members of selected universities and colleges in the region. Structural Equation Modeling (SEM) is used to validate the measurement model and examine the structural relationships among the study constructs. The findings indicate that digital transformation plays a significant role in enhancing educational quality. Digital infrastructure provides the technological foundation for effective academic delivery, while faculty digital competence strengthens the integration of digital tools into pedagogical practices. Institutional support facilitates the successful implementation of digital initiatives, and technology-enabled teaching practices contribute to improved learning experiences and academic engagement. Collectively, these dimensions demonstrate a positive influence on educational quality within higher education institutions. By providing empirical evidence from a region that has received limited scholarly attention, this study extends the literature on digital transformation in higher education and offers a context-specific understanding of how digital capabilities contribute to educational improvement. The findings provide valuable insights for policymakers, institutional leaders, and quality assurance agencies seeking to strengthen educational quality through strategic digital transformation initiatives. The study also highlights the importance of developing digitally capable institutions to support inclusive, effective, and sustainable higher education in India.